2008
DOI: 10.1007/s12262-008-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel enterocutaneous fistulae: the merits of early surgery

Abstract: Background The treatment of patients with small bowel enterocutaneous fi stulas is complex and a challenge for every surgeon. The mortality and morbidity associated with only conservative management is often high and expensive because most patients cannot afford prolonged parenteral nutrition which itself carries a high incidence of complications. Although operations are diffi cult if performed early they may be lifesaving in our situation. The focus of our study was to determine whether, in patients with fi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…14 Ugochukwu at Enugu (74.2%) 15 and Dodiyi-Manuel et al (75%) 16 in Southern Nigeria, and Chalya et al (65.6%) 17 in Tanzania, also reported a similar high spontaneous healing rate following enteral feeding. Gupta et al (67%) 18 and Visschers et al (87%) 19 reported similar high healing rates with use of enteral and parenteral feeding. However, some workers have reported lower healing rates.…”
Section: Discussionmentioning
confidence: 80%
“…14 Ugochukwu at Enugu (74.2%) 15 and Dodiyi-Manuel et al (75%) 16 in Southern Nigeria, and Chalya et al (65.6%) 17 in Tanzania, also reported a similar high spontaneous healing rate following enteral feeding. Gupta et al (67%) 18 and Visschers et al (87%) 19 reported similar high healing rates with use of enteral and parenteral feeding. However, some workers have reported lower healing rates.…”
Section: Discussionmentioning
confidence: 80%
“…This was very much similar to that analysis done by Gupta M Mortality was higher in ≥60 year's group (28.5%) than in <60 years group (8%), but the data was statistically significant (p value-0.1548). 8 Octreotide was used in all cases of high output fistulas and it was found that there was a significant reduction in fistula output within the first 48 hrs. Significant reduction in fistula output after octreotide has also been reported by Paran et al, Sleth et al and Kocak et al [9][10][11] Although somatostatin effectively reduces the fistula output, the rate of spontaneous closure is not changed.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical closure rates were higher than spontaneous closure rates in both populations. 8 Surgical intervention was performed after a median period of 15 days (rage 3-34 days) from the occurrence of the fistula. The goal was to perform surgery as soon as the patient condition was stabilized and any septic and any septic foci had been adequately treated.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have already been reported to affect the rate of spontaneous healing, including surgical etiology and low output, with no associated abscess or comorbidity 14. However, a few studies have shown a higher fistula healing rate 16–18. The highest healing rate of 81% was reported by Gupta et al,16 67% was reported by Harriman et al,17 and 53.3% was reported by Nursal Tarık et al18 This difference in reported rates is likely related to the experience and skill of the surgeon or the patient’s condition 14…”
Section: Discussionmentioning
confidence: 99%